(untitled) (New Jersey, 2003)
The revised full papers presented were carefully reviewed and selected for inclusion in the volume. The book is divided in sections on indoor wireless networking, multiple access techniques for wireless ad-hoc networking, telephony over packet switched networks, IP networks versus conventional switched networks, mobility management and access techniques, and mobility support in IP.
Keywords: Wireless communication systems,Mobile communication systems,Hệ thống viễn thông không dây,Hệ thống viễn thông di động; Congresses,Congresses,Hội thảo,Hội thảo